The Dispute Over The Nile River Involving The Grand Ethiopian Renaissance Dam - Souza, Veronica Honorio Gomes de; Jara, Esteban Paiva (Universitas Airlangga, 2023)
This study examines the complex conflict over the Nile River, focusing on the Grand Ethiopian Renaissance Dam (GERD) and its implications for regional socio-economic development. The research adopts a systems perspective to analyze the dynamics between Egypt, Sudan, and Ethiopia. It highlights the challenges of water management in the Nile River Basin, shared by eleven African countries, and delves into the geopolitical, environmental, and socio-economic factors at play. The research team, composed of Latin American scholars, acknowledges their outsider perspective and strives to incorporate a wide range of views. The findings discuss the historical treaties, current negotiations, and the importance of a balanced agreement that considers the interests of all parties, the threat of climate change, and sustainable water management practices. The study concludes with insights that could inform similar disputes in other transboundary river basins and underscores the urgency for cooperative solutions to prevent humanitarian crises. Keywords: Nile River, GERD, Causal Loops, System Perspective